Securing disunion: Young people's nationalism, identities and (in)securities in the campaign for an independent Scotland. (November 2016) - Botterill, Kate; Hopkins, Peter; Sanghera, Gurchathen; Arshad, Rowena
Abstract: This paper explores ethnic and religious minority youth perspectives of security and nationalism in Scotland during the independence campaign in 2014. We discuss how young people co-construct narratives of Scottish nationalism alongside minority ethnic and faith identities in order to feel secure. By critically combining literature from feminist geopolitics, international relations (IR) and children's emotional geographies, we employ the concept of 'ontological security'. The paper departs from state-centric approaches to security to explore the relational entanglements between geopolitical discourses and the ontological security of young people living through a moment of political change. We examine how everyday encounters with difference can reflect broader geopolitical narratives of security and insecurity, which subsequently trouble notions of 'multicultural nationalism' in Scotland and demonstrate ways that youth 'securitize the self' (Kinnvall, 2004 ). The paper responds to calls for empirical analyses of youth perspectives on nationalism and security (Benwell, 2016 ) and on the nexus between security and emotional subjectivity in critical geopolitics (Pain, 2009; Shaw, Powell, & De La Ossa, 2014 ). Funded by the Arts and Humanities Research Council (AHRC), this paper draws on focus group and interview data from 382 ethnic and religious minority young people in Scotland collected over the 12-month period of the campaign. Highlights: Security is theorised as embodied, emotional, intimate and multi-scalar. Religious and ethnic minority youth experience multiple securitizing processes that shape subjectivity. Young people's (in)securities are integral to understanding global and national securities. Uses concept of ontological security to Integrate feminist geopolitics, international relations and children's geography. Referendum politics as a research site to explore the geographies of security.